Natural Polysaccharide based Nanoparticles for Drug/Gene Delivery - Sara Salatin, Mitra Jelvehgari (Tabriz University of Medical Sciences, 2017)
The dawn of the state-of-the-art methods of drug/gene delivery, nano-based delivery systems for delivery of pharmaceutically active agents into the target sites in the body have been developed. Among these, a concerted effort has been directed towards the development of biodegradable/biocompatible nanomaterials with the high potential benefits of passive/active targeting and reduced undesirable side effects. Since polysaccharides offer a large number of available reactive groups, specific targeting could be obtained by the surface coating of nanoparticles with targeting ligands. On the other hand, mucoadhesive properties of polysaccharides can be used for prolonging the residence time of delivery systems at the site of absorption. This study reviews a number of important polysaccharides with a perspective on the challenges, advantages, and disadvantages of their applications as drug/gene delivery systems.